Biomedical Applications of Polycaprolactone (PCL) Composites: Structure, Properties, and Future Prospects - Subhedar, Prajakta; Padmanabhan, Divya; Agrawal, Richa (Journal of Research Updates in Polymer Science, 2025)
Polycaprolactone (PCL) is a semi-crystalline, biodegradable aliphatic polyester that has emerged as a versatile biomaterial for tissue engineering, drug delivery, and regenerative medicine applications due to its exceptional biocompatibility, controlled degradation kinetics (2-4 years in vivo), and FDA approval status for multiple medical devices. Despite these advantages, pure PCL exhibits significant limitations including low mechanical strength (16-24 MPa tensile strength), hydrophobic surface properties (water contact angle 80-90°), and minimal bioactivity, which restrict its clinical utility in load-bearing and cell-interactive applications. To address these shortcomings, researchers have developed PCL-based composite systems by incorporating bioactive ceramics (hydroxyapatite, β-tricalcium phosphate), natural polymers (collagen, chitosan, gelatin), synthetic polymers (PLA, PLGA), and nanomaterials (carbon nanotubes, graphene oxide) to create multifunctional biomaterials with enhanced properties. This comprehensive review analyzes PCL composite development over the past two decades, emphasizing fabrication techniques including electrospinning, 3D printing, solvent casting, and melt blending, which enable precise control over scaffold architecture and functionality. Comparative analysis with other biodegradable polymers (PGA, PLGA) reveals PCL’s unique advantages in long-term applications, with studies demonstrating >90% cell viability, 65% bone regeneration in animal models, and sustained drug release profiles extending 6-8 weeks. Recent innovations include smart, stimuli-responsive PCL systems for targeted therapy, gene delivery platforms, and bioprinting applications that have advanced from laboratory research to clinical trials, with several PCL-based products (Neurolac®, Osteoplug®) receiving regulatory approval. Current challenges include manufacturing scalability, long-term biocompatibility assessment, and complex regulatory pathways for multi-component systems. Future developments focus on integrating artificial intelligence for scaffold design, 4D printing technologies for dynamic structures, and multidisciplinary approaches combining materials science with precision medicine. This review demonstrates that PCL-based composites represent a transformative class of biomaterials with customizable properties that bridge fundamental research and clinical translation, positioning them at the forefront of next-generation biomedical technologies.